Getting Real about Sex Addiction: A Psychodynamic Approach to Treatment - Daniels, Graeme; Farley, Joseph P. (Rowman & Littlefield Publishers, 2022)
As the controversial field of sex addiction treatment reaches for legitimacy across the disciplines of medicine, psychiatry and psychotherapy, Getting Real about Sex Addiction: A Psychodynamic Approach to Treatment applies psychoanalytic framework to concepts of addiction and sex, as well as related concepts of personality and attachment development. Authors Graeme Daniels and Joe Farley explore the intersection of sex and culture and address social undercurrent relating to gender, such as objectification and sexual aggression and how those influence conceptualization goals and procedures in treatment. Through a number of case illustrations and vignettes, this text demonstrates psychodynamic method across treatment contexts, in formats of individual, couples, and group therapy. The result is a work that critiques theoretical, intervention, and gender biases that have infiltrated this important yet embattled field, and provides a fresh, alternative approach from a source with the oldest pedigree in modern psychology.